Study of Decomposition of Chemical Warfare Agents Using Solid Decontamination Substances: An Approach to Assess Degradation Efficiency - Capoun, Tomas; Krykorkova, Jana (Current Advances in Chemistry and Biochemistry Vol. 10, 2021)
Decontamination of chemical warfare agents is an important measure leading to elimination or reduction of effects of those substances on persons. Solid decontamination (degradation) sorbents that decompose dangerous substances belong among modern decontamination substances. The aim of the study was to design a procedure for monitoring the degradation of chemical warfare agents using such sorbents. Degradation of soman, VX and sulphur mustard (chemical warfare agents) was monitored using FTIR spectrometry with the ATR technique. During the development and validation of the process, bonds were found in the substance molecule that decomposed and the positions of the absorbance bands that corresponded to the vibration of that bond. The evaluation of degradation efficiency procedure for sorbents on chemical warfare agents was designed based on this study. We present the result of the measurements graphically as the time dependence of the distributed CWA ratio, and the reaction time required to decompose 50 and 90% of the original amount of the substance.